MK2 drives progression of pancreas and colon cancers by suppressing CD8+ T cell cytotoxic function and is a potential immunotherapy target - Jacenik, Damian; Lebish, Eric J.; Beswick, Ellen J. (Frontiers in Immunology, 2023)
Immune cell composition is a critical component of the tumor microenvironment, which has an impact on immunosuppression and progression of cancer. T cells are one of the major immune cell types responsible for tumor cell killing employing receptor-ligand mediated apoptosis and/or releasing lytic granules among others. Accumulating evidence highlighted that adoptive transfer of activated or modified immune cells can enhance anti-tumorigenic immune responses and serve as promising therapy for patients with cancers. The MK2 is serine/threonine protein kinase which controls production of numerous cytokines/chemokines involved in tumorigenesis. However, limited efforts have been made to learn how MK2 may affects cytotoxic T cell action in the microenvironment of gastrointestinal cancers. To explore the therapeutic potential of MK2 in the immune response mediated by cytotoxic T cells, mice with PK5L1940 and BRAF cells-derived allograft tumors were treated with WT or MK2 knockout CD8+ T cells. The phenotype of cytotoxic T cells with MK2 depletion were evaluated in vitro. Immunofluorescence staining, real-time PCR and multiplex analysis were utilized to estimate the expression of apoptotic and lytic factors. Here, we show that CD8+ T cells with MK2 depletion prevent gastrointestinal cancer growth, which is accompanied by enhanced expression and secretion of factors related to apoptosis. Moreover, we found that depletion of MK2 lead to hyperactivation of cytotoxic T cells and enhanced anti-tumor immunity. Overall, we documented that MK2 drives the progression of gastrointestinal cancers prevents immune response generated by CD8+ T cells suggesting potential implications of MK2 in the immunotherapy of gastrointestinal cancers.